2021
DOI: 10.11591/ijere.v10i4.21767
|View full text |Cite
|
Sign up to set email alerts
|

Digital citizenship trend in educational sphere: A systematic review

Abstract: <span>The surge of information in the digital age has impacted social problems. Accordingly, digital citizenship had been discussed mostly within topics related to digital security, IT education. A systematic review is needed to provide an overview for educators and policymakers in Indonesia to address ethical and technical issues to improve the online environment safely. However, there are limited studies that systematically review the existing literature on implementing digital citizenship in Indonesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
1
5
0
3
Order By: Relevance
“…This is also in line with E-safety Support [11] which stated digital literacy was a key of teaching to improve the skills, knowledge, and understanding of technology for the students who would pursue tertiary education and later enter the workforce. This is also in line with research [30] that stated digital literacy was a digital citizenship consisted of digital literacy.…”
Section: Discussionsupporting
confidence: 90%
“…This is also in line with E-safety Support [11] which stated digital literacy was a key of teaching to improve the skills, knowledge, and understanding of technology for the students who would pursue tertiary education and later enter the workforce. This is also in line with research [30] that stated digital literacy was a digital citizenship consisted of digital literacy.…”
Section: Discussionsupporting
confidence: 90%
“…To overcome the problem, we conducted research using a systematic literature review (SLR) procedure with Publish or Perish software. The SLR method can help summarise the latest knowledge on a particular topic systematically and transparently to answer research questions, especially about the definition and conceptual model of genetics literacy [33]- [35]. The stages of the SLR procedure adopt the framework of Arksey and O'Malley [36], which consists of five main steps, namely: i) identifying the research questions, ii) identifying relevant studies, iii) eligibility criteria, iv) study selection, v) collating, summarising, comparing, and reporting the results.…”
Section: Methodsmentioning
confidence: 99%
“…Barassi (2017), Emejulu and McGregor (2019), and Mahadir et al (2021) confirmed the impact of technology on those who deal with it, so they are considered good "digital citizens," they spend more time in their digital world than they do with their family and friends, which affects their lifestyle. Prasetiyo et al (2021) and Al-Thubetat et al (2023) found that individuals in the digital age consider the Internet as an important means of carrying out most of their tasks. Although the use of digital technology is popular with young people, they are not fully aware of its potential.…”
Section: Literature Reviewmentioning
confidence: 99%